Pimodivir Treatment in Adult Volunteers Experimentally Inoculated with Live Influenza Virus: A Phase IIa, Randomized, Double-Blind, Placebo-Controlled Study. Issue 4 (May 2018) - Trevejo, Jose M; Asmal, Mohammed; Vingerhoets, Johan; Polo, Ramon; Robertson, Sarah; Jiang, Ying; Kieffer, Tara L; Leopold, Lorant
Background: Pimodivir (formerly JNJ-63623872) is a novel, non-nucleoside polymerase complex inhibitor with in vitro activity against influenza A virus, including pandemic 2009 H1N1, H7N9, H5N1 strains as well as neuraminidase- and amantadine-resistant strains. Methods: Randomized, double-blind, placebo-controlled, Phase IIa study. Healthy volunteers ( n =104) were inoculated with an influenza A/Wisconsin/67/2005 (H3N2) challenge virus. 72 received pimodivir and 32 placebo. Pimodivir was dosed for 5 days once daily from 24 h after viral inoculation at four dose levels: 100 mg, 400 mg, loading dose 900/600 mg and loading dose 1, 200/600 mg. Results: Pimodivir significantly reduced viral shedding (area under the concentration versus time curve [AUC] measured by 50% tissue culture infective dose [TCID50 ] or qRT-PCR) versus placebo as measured by cell culture assay in the pooled analysis (Jonckheere-Terpstra dose-response trend test [ P =0.036]). Reductions were observed in viral shedding (AUC, duration and peak measured by grade), influenza-like symptoms (AUC, duration and peak measured by grade) and clinical symptoms (duration and peak measured by grade) for all pimodivir groups versus placebo, significantly so for the 1, 200/600 mg group. In the 1, 200/600 mg group viral shedding (AUC) by qRT-PCR was 0.45 versus 18.4 log10 copies/ml*day for pooled placebo ( P =0.014). Pimodivir was generally safe and well-tolerated with no serious adverse events or adverse events leading to discontinuation. Conclusions: Pimodivir has potential to not only reduce viral load but to have a clinical impact on patients as a novel treatment for influenza A virus infection. Further trials are therefore warranted to assess pimodivir.